Brexit Calling! Aftermath in the Pharmaceutical Industry - Tsangari, Haritini; Mantara, Ioanna (International Journal of Business, Economics and Management, 2020)
This paper aims to examine the impact of the Brexit referendum on the financial performance of the pharmaceutical industry in the United Kingdom. We analyze daily data for the period 1/2000-10/2019, for the two largest British pharmaceutical firms, GlaxoSmithKline and AstraZeneca, as well as two European competitors, the Swiss Novartis and the German Bayer. We perform returns and volatility analysis, financial ratio analysis and regression analysis. Our empirical results are heterogeneous among firms, pinpointing strengths and weaknesses of the pharmaceutical firms. The Brexit decision has had a significant, positive effect on the stock returns of the two British firms, a negative effect for Bayer and no effect for Novartis, while lagged returns are significant only for the European firms. At least in the short-run, both British firms have gained considerably from the depreciation of the sterling and should aim to expand their overseas network and avoid prospective trade barriers and regulatory issues.